2015
DOI: 10.1016/j.tet.2015.05.063
|View full text |Cite
|
Sign up to set email alerts
|

Enantiospecific gram scale synthesis of (S)-eleagnine

Abstract: a b s t r a c tAn alternative route to the tetrahydro-b-carboline scaffold is presented, where the amino acid L-alanine was transformed to (S)-eleagnine in a straightforward and scalable manner yielding the target compound in enantiopure form on gram scale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…In 2015, Lood et al reported the new enantiospecific gram-scale synthesis of ( S )-eleagnine/(−)-tetrahydroharmane ( 2 ) ( Scheme 2 ) [ 110 ]. Their synthesis started from the previously modified amino acid methyl ester 82 , which included the appropriate chirality.…”
Section: Natural Products Containing a Simple β-Carboline Skeletonmentioning
confidence: 99%
“…In 2015, Lood et al reported the new enantiospecific gram-scale synthesis of ( S )-eleagnine/(−)-tetrahydroharmane ( 2 ) ( Scheme 2 ) [ 110 ]. Their synthesis started from the previously modified amino acid methyl ester 82 , which included the appropriate chirality.…”
Section: Natural Products Containing a Simple β-Carboline Skeletonmentioning
confidence: 99%
“…Phenanthroindolizidines (50 [71,72]), phenanthroquinolizidines (51 [72]), tetrahydroprotoberberines (53 [67,68]), pyrroloisoquinolines (55 [69,70]), and diketopiperazine-fused THIQs (65 [73], vide infra) embody the tetrahydroisoquinoline skeleton, while indolizinoindoles (57 [74,75]), THBC-imidazolinediones (59 [76]), THBC-piperazinedione (61 [77,78]), the tetracyclic indole alkaloids (S)-harmicine (pyrrole-fused THBC, [66,79]), and (S)-eleagnine (1-methyl THBC, [66,80] represent the THBC-containing polyheterocycles. The additional ring can be already present in the imine substrate before the P-S reaction (type A) or can be built on the THIQ/THBC skeleton exploiting the functionality of some substituents (type B).…”
Section: Polyheterocyclesmentioning
confidence: 99%
“…The synthesis contemplated the de novo construction of the indole ring with the appropriate substituents to give the PSR in the final step. A gram-scale total synthesis of (S)-eleagnine [53] and (S)-harmicine [54] in enantiopure form (>99% ee) was achieved.…”
Section: Chiral Auxiliariesmentioning
confidence: 99%